Reading keys : skills and strategies for effective reading - Craven, Miles
Reading keys new edition is designed for adult and young adult learners of English at the high beginner to high intermediate levels. Each of the three levels has 16 topic-based units organized into eight themes. Texts to study may be selected by topic, genre, reading skill, or vocabulary skill.